2018
DOI: 10.4236/gep.2018.64008
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial Assessment of the Impact of Urban Sprawl in Akure, Southwestern Nigeria

Abstract: This study analyzed trend and examined the factors responsible for urban sprawl in Akure with a view to develop a user-friendly geospatial database for monitoring urban sprawl in the study area. Medium resolution satellite imageries derived from Landsat (TM) and (ETM+) comprising of four dates (1986, 1991, 2002 and 2011) were analyzed. The results revealed that built-up area increased rapidly by 43.31% from 5857.54 hectares in 1986 to 8394.21 hectares in 1991. It further increased by 72.02% from 8762.76 hecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The overall change over the 1991 to 2021 period showed a decrease of about 75km 2 , representing about 62% decrease in the size of the LUC. The overall decrease in the area of this LUC is expected as urban growth is very well known to be causing decline in areas under farming activities [60][61][62][63][64][65][66][67][68][69][70][71].…”
Section: Resultsmentioning
confidence: 99%
“…The overall change over the 1991 to 2021 period showed a decrease of about 75km 2 , representing about 62% decrease in the size of the LUC. The overall decrease in the area of this LUC is expected as urban growth is very well known to be causing decline in areas under farming activities [60][61][62][63][64][65][66][67][68][69][70][71].…”
Section: Resultsmentioning
confidence: 99%
“…RS is a method of collecting data at a distance from the object (earth's surface and atmosphere) under study through the use of electromagnetic sensors often by the use of satellites or aircraft (Schowengerdt, 2007). GIS and RS have been widely used in urban mapping and monitoring of urban development (Owoeye and Ibitoye, 2016;Usman et al, 2018;Popoola et al, 2020;Sharifi, 2020;Mohammadi and Sharifi, 2021;Saha et al, 2022;Moradi and Sharifi, 1 https://earthexplorer.usgs.gov/ 2023). After the pragmatic selection of the Landsat images (raster datasets) for this study, the image processing started with band combinations to develop a False Color Composite (FCC) of the images.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to urban (spatial) growth and modeling, Owoeye and Ibitoye (2016) explored land use change detection in Akure using remote sensing. Consequently, Usman et al (2018) investigated the impact of urban sprawl in Akure with geospatial assessment, while Eke et al (2017) analyzed the urban expansion of Akure using geographic information systems (GIS). Exploring the relationship between urban health and city growth, Alabi (2022) observed the financial and health toll of urban sprawl on residents of Akure, while Popoola et al (2020) investigated how micro-climate is influenced by urban growth in Akure.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar study, Mengistu and Salami (2007) attributed continued population expansion (Kuddus et al, 2020) as one of the key factors causing spatial growth of Built up and the related pressure on the available land resources and other land use types prompting land use class transition. Several studies have shown that impervious surfaces tend to grow due to urbanization in most parts of the country (Oyinloye & Kufoniyi, 2011;Obiakor et al, 2012;Jesuleye et al, 2013;Mahmoud et al, 2016;Usman et al, 2018;Wang et al, 2018;Wang et al, 2020). Haphazard development can be observed in the study area which is attributed to the uncontrolled increase in impervious surfaces coupled with the absence of well-defined policy implementation for impervious surfaces.…”
Section: Discussionmentioning
confidence: 99%